Comparative Study of Hearing Improvement of Type 1 Tympanoplasty Using Temporalis Fascia and Conchal Cartilage as Graft Material - Bhardwaj, Bhanu (Indian J Otolaryngol Head Neck Surg, 2018)
Tympanic Membrane perforation is a common cause of hearing loss. Various surgical techniques with different types of graft materials have been described for the treatment of perforations. The conchal cartilage and temporalis fascia graft are most widely used. We conducted a prospective Randomized control trial at Sri Guru Ram Das Institute of Medical Sciences and Research to compare the post operative hearing outcomes between the patients of safe CSOM (n = 40) using temporalis fascia (n = 20) and conchal cartilage (n = 20). It was found that the AB gap closure at 2 months post-operatively was 11.55 ± 8.173 for conchal perichondrium group as compared to 10.49 ± 9.069 for temporalis fascia group. At 6 months the AB gap closure was 14.98 ± 9.915 for conchal cartilage group as compared 11.41 ± 8.288 db for temporalis fascia group. Thus hearing improvement was better for conchal cartilage group both at 2 and 6 months but the comparison of the AC gain at the end of 6 months and subjective improvement in hearing between the two techniques was not statistically significant owing to the small sample size of the study. Both Temporalis fascia and conchal cartilage with perichondrium were acceptable graft material for successful closure of tympanic membrane perforation, hearing improvement was better with conchal cartilage group.